The limits of resilience in US community responses to recent drought events. Issue 2 (15th March 2019) - Jedd, Theresa M.
ABSTRACT: Drought threatens many facets of community life, including food security, agricultural and tourism livelihoods, recreation, esthetic appeal, and social cohesion. Many policy responses to a drought crisis are enacted at the municipal level, including voluntary water conservation, burn bans, outdoor watering restrictions, municipal water source expansion, and drought contingency plans. Though communities have many reasons to limit their vulnerability to future drought events, it is questionable whether these measures do. In a comprehensive survey of more than 450 news media reports on drought response in communities across the United States, this study defines 27 common response approaches. Results show that responses tend to be short-term emergency coping measures. Temporary water restrictions may not leave communities prepared to address future water crises. Furthermore, restrictions can create tension amongst levels of governance. Recommendations based in resilience theory suggest that collaboration, engagement, and forward-looking planning processes are necessary to address community drought vulnerability.